A Body Worth Defending. Opening Up a Few Concepts: Introductory Ruminations - Ed Cohen (Avant, 2012)
The following text is an introduction to Ed Cohen’s book A Body Worth Defending: Immunity, Biopolitics and the Apotheosis of the Modern Body. Author investigates the way in which immunology influences the perception of both the human body, and political entities, demonstrating that contemporary conceptualizations of these phenomena exist in a double bind. The historical framework Cohen applies allows for tracing the history of the metaphor of immunity in politics and medicine.